2002
DOI: 10.1046/j.1365-2265.2002.01460.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipoprotein changes following IGF‐I normalization using a growth hormone receptor antagonist in acromegaly

Abstract: Active acromegaly is associated with lowered mean serum TC and LDL. Successful management using pegvisomant increases lowered baseline serum TC and LDL levels, restoring the distribution of values to that of the general population, and improves insulin resistance. These findings are consistent with the reported lipoprotein changes following GH administration to normal and GH-deficient individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 74 publications
6
23
0
4
Order By: Relevance
“…Conflicting data exist about the effect of acromegaly on lipid levels. Some studies indicate a worse lipid profile in active acromegaly (9,24) while other authors reported better values (22,25,26) and a worse profile after therapy (26). We found total cholesterol and triglycerides to be significantly lower both in controlled and non-controlled acromegaly.…”
Section: Discussionsupporting
confidence: 51%
“…Conflicting data exist about the effect of acromegaly on lipid levels. Some studies indicate a worse lipid profile in active acromegaly (9,24) while other authors reported better values (22,25,26) and a worse profile after therapy (26). We found total cholesterol and triglycerides to be significantly lower both in controlled and non-controlled acromegaly.…”
Section: Discussionsupporting
confidence: 51%
“…Serum total kolesterol düzeylerinin arttığını, normal olduğu-nu ve düştüğünü gösteren çalışmalar vardır [8]. LDL normal olabilmesine rağmen artmış kardiyovaskü-ler mortalite ile ilişkili olan küçük/yoğun LDL, total LDL'nin hakim kısmını oluşturmaktadır [23].…”
Section: Discussionunclassified
“…Buna bağlı olarak hepatik VLDL yapımında artış ve lipoprotein lipaz düzeyinde azalma olabilir. Akromegalide HDL düzeylerinin düştüğü gösterilmiştir [8,9].…”
Section: Introductionunclassified
“…Esse achado poderia representar tanto o efeito direto dos níveis de GH sobre esta proteína quanto o refl exo de possível defi ciência relativa de GH nos pacientes tratados. Em estudo com 20 acromegálicos, avaliados antes e após o pegvisomanto, encontraram-se níveis iniciais reduzidos de colesterol total e LDL, os quais aumentaram após o tratamento (68). Já a Lp-a, inicialmente elevada na maioria dos pacientes, diminuiu com o tratamento.…”
Section: Distúrbios Cardiovasculares Na Acromegaliaunclassified